Editorial: calcium homeostasis in skeletal muscle function, plasticity, and disease - Mosqueira, Matias; Brinkmeier, Heinrich; Jaimovich, Enrique (Frontiers in physiology, 2021)
Editorial: Calcium Homeostasis in Skeletal Muscle Function, Plasticity, and Disease
Gesehen am 31.05.2021